Regular Analysis of Aero-Diesel Piston Engine between Combustion Chamber Size and Emission - Zhongjian Pan; Yu Deng; Lizhi Cheng (International Journal of Aerospace Engineering)
The emission of aero-engines has been a focused issue, studying the regular of combustion chamber size on engine emission performance, with an aviation diesel piston engine as the object of study; the numerical model of diesel combustion spray and emission model are analyzed; and the dynamics grid of the combustion chamber is meshed by FIRE software, analyzing the relationship between the reentrant diameter, the maximum depth of the combustion chamber, and the emission generation, comparing the NOx and soot emissions under different combustion chamber sizes. The results show that reducing appropriately the reentrant-max diameter ratio and max diameter-max depth ratio of the combustion chamber can reduce emissions when maintaining the same compression ratio by adjusting the mid-depth. Modifying the geometry parameters of the combustion chamber to verify regularity, it was found that engine NOx emission decreased by 28% and soot emission decreased by 3.6% when changing the size, which verified the correctness of regular analysis.